POPULATION STRUCTURE OF LOKAN (Polymesoda expansa) IN THE REHABILITATION MANGROVE ECOSYSTEM OF ANAK SETATAH VILLAGE, MERANTI ISLANDS REGENCY - Fitri, Sri Sumarni; Zulkifli, Zulkifli; Nasution, Syafruddin (Asian Journal of Aquatic Sciences, 2025)
Polymesoda expanse belongs to the class of Bivalves found in mangrove forests; their habitat is between mangrove roots on muddy substrates, sandy mud and mangrove litter. This study aims to determine the abundance of P. expansa in Anak Setatah Village, Kepulauan Meranti Regency, examine the size-frequency distribution, and investigate the distribution pattern in the area. The study was conducted in October 2024 by using a survey method. The sites were located in the coastal waters of Anak Setatah Village. Station I is near residential areas, Station II is near fishing ports, and Station III is near agricultural areas. A one-way ANOVA was used to analyse differences in abundance between stations and zones. The results revealed significant differences in abundance, with Station II (near fishing ports) exhibiting the highest abundance and Station I (near residential areas) showing the lowest. The middle zone had the highest abundance among the zones. Furthermore, based on the results of the ANOVA test (p< 0.05), there is a significant difference in abundance between stations. The LSD test revealed a substantial difference in abundance between stations I and II, and stations I and III. However, no significant difference was found from the ANOVA test, with a p-value of 0.125 > 0.05, indicating that there was no significant difference in abundance between zones. The size frequency of P. expansa ranged from 17.6-64.8 mm, and the distribution pattern was clustered